EVALUATION OF ONLINE LEARNING ON THE LEVEL OF UNDERSTANDING OF TADRIS IPA STUDENTS OF IAIN BENGKULU SEMESTER 5A IN BIOMOLECULE AND METABOLISM COURSES - Sulikah Septi Herawati; Arni Apriyanti; Widya Amandra; Ahmad Walid (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
This study aims to determine the level of understanding of science tadris students in semester 5A at IAIN Bengkulu in the biomolecule and metabolism course which is carried out in an online system. This research was conducted by giving online questionnaires/questionnaires to respondents. The type of questionnaire given is an open questionnaire, in which the respondent is free to fill in the answers according to their wishes. Based on the questionnaire, it was found that students had difficulty understanding biomolecule and Metaboism courses. The difficulty in understanding the material that has been provided online, which is deemed ineffective, this can have an effect on the low learning achievement of Tadris IPA 5A students at IAIN Bengkulu. For this reason, there is need for awareness from students to improve the learning process outside class hours, this aims to maximize student understanding of the materials and assignments given by the lecturer in order to maintain the stability of the value of each student.